Female professional educators in the Peruvian life - Bustamante Quiroz, Elsa (2018)
This article presents an analysis of the participation of female professional educators in Peruvian life in the past century’s last decades and the first decades of the current century through the experience and vision of three female representatives. This research was done using a biographical approach and a semi-structured interview. In conclusion, although the female presence has been relevant, women as a group have primarily developed in the teaching field but not in social politics. The pathways of those who have achieved important roles should motivate the enhancement of capabilities and conditions for women to have more significant roles.